Water use Pattern of Rural Community in Gangetic West Bengal - A Case Study - Roy, Arijit (Journal of Rural Development, 2012)
Water is the most precious natural resource acting as the lifeline of the rural community. It can be highly productive and support prosperous communities if properly used. This paper attempts to explore the water use pattern of rural community in Gangetic West Bengal. Primary data were collected in the East Midnapore district of West Bengal during 2008-2009. It has been observed that the level of per capita income does have a positive influence on the level of per capita domestic water consumption. Also, the proximity of the water source does increase domestic water consumption. Agriculture is the major occupation with the highest water dependence. It has also been found that water consumed for agriculture is directly influenced by the level of per capita income, the proximity of water source and water-intensive cropping pattern.